Workflow disruptions and provider situation awareness in acute care: An observational study with emergency department physicians and nurses. (October 2020) - Weigl, Matthias; Catchpole, Ken; Wehler, Markus; Schneider, Anna
Abstract: Background: The fast-paced and rapidly changing environment of an Emergency Department (ED) requires providers to have a high level of situation awareness (SA). However, acute clinical care also encompasses a multitude of interruption-laden work processes that might degrade SA. It is therefore important to understand how frequent interruptions affect ED provider cognition in general and SA in particular. Objective: We aimed to examine how sources and contents of provider workflow interruptions influence situation awareness of ED physicians and nurses. Methods: This prospective, multi-method study combined standardized observations, self-reports of ED providers, and ED administrative data of staffing and patient load. Expert observers identified ED providers' workflow interruptions during 90min observation sessions. Afterwards, each provider reported perceived disruptiveness and situation awareness. Controlling for patient load, patient acuity and staffing, we conducted regression analyses to explore prospective associations between interruptions and provider outcomes. Results: During 74 observation sessions of overall 110h and 40min, we observed 1205 workflow interruptions (mean rate: 10.9 interruptions/hour). Provider situation awareness was fairly high (M = 7.10; scale 0–10) with no difference between ED physicians and nurses. After controlling for ED workload data, we observed that high rates of interruptions were associated with lower levels of situation awareness (β = −0.27). Further analyses revealed that particularly interruptions by telephone/beeper, technical malfunctions as well as interruptive communication related to completed cases were correlated to low SA. Discussion: This study in a naturalistic ED setting shows that ED physicians and nurses continuously cope with disruptions and interruptions. Our findings reveal that highly interruptive workflow environments impede providers' situation awareness. Moreover, it sheds light on specific sources and contents of interruptions that influence providers' SA in acute care. Conclusion: Frequent workflow interruptions can degrade ED providers' situation awareness. A deeper understanding of how avoidable and unavoidable interruptions affect provider cognitions with particular focus on social and technology-related disruptions is required. Further emphasis should be placed on the effective application of work re-design in this context to foster safe and efficient patient care. Graphical abstract: Image 1 Highlights: Acute care providers need to maintain situational awareness in often fast-paced and rapidly-changing work environments. We investigated the effects of workflow interruptions on provider cognition in an Emergency department. High rates of interruptions were significantly associated with low levels of ED providers' situation awareness. Harmful effects of workflow interruptions should be mitigated to support provider cognition and promote patient safety.